Does circumcision change uroflowmetry parameters? - Sancar, Serpil; Kırlı, Elif (The European Research Journal, 2020)
Objectives: The benefits of circumcision, which is one of the most frequently performed surgical procedures, are controversial. In our study, before and after circumcision, uroflowmetry parameters were compared to evaluate the effects of circumcision on voiding. Methods: Children between the ages of 5-15 years who applied to the outpatient clinic for voluntary circumcision and who did not have underlying diseases and voiding problems were included in the study. Circumcision was performed by specialist in sterile conditions under general anesthesia. Uroflowmetry was evaluated by voiding volume, voiding time, maximum flow rate, average flow rate, shape of the curve. The pre-circumcision and post-circumcision uroflowmetry results were compared statistically. Results: Fifty patients with a median age of seven years (range: 5-10 years) were included in the study. When uroflow parameters were compared in our study, the maximum flow rate, mean flow rate and the time to maximum flow rate were found significantly different (p < 0.05). The plateau pattern was detected in 30% of patients before circumcision, while in 8% of patients after circumcision. Conclusions: Circumcision performed by specialists under sterile conditions has positive effects on uroflow parameters.